Odpowiedzi

Najlepsza Odpowiedź!
2010-03-07T21:59:35+01:00
A) 2a + 3 - a +6 + 7a dla a= -2
8a+9 = 8 * (-2) +9 = -16+9 = -7

b) 2z + t - 3z+ 4t - 1 dla z= 5 i t = 0,1
-z+5t = -5 + 5 * 0,1 = -5 + 0,5 = -4,5

c) 13x - 2y + 7 - 9x + y - 4 +x-3 dla x=0,2, y =-1
5x-y+4 = 5*0,2 - (-1) +4 = 1+1+4 = 6

d) n²+n-7 +3n²-n-9-n+16 dla n= -½
n²+3n² +n-n-n-7-9+16= 4n²-n = 4 *(-½) -(-½) =
= -2+0,5 = -1,5


54 4 54
2010-03-07T22:01:37+01:00
2010-03-07T22:07:18+01:00
A) 2a + - a +6 + 7a dla a= -2
9a + - a +6
8a+6
8*-2+6=-16 + 6= -10
b)2z + t - 3z+ 4t - 1 dla z= 5 i t = 0,1
2z - 3z+ t + 4t - 1
-z+5t-1
-5+0,5 -1=-6 +0,5= -5,5

c) 13x - 2y + 7 - 9x + y - 4 +x-3 dla x=0,2, y =-1
13x +x- 9x- 2y+ y + 7 - 4 -3
14x-9x-y
5x-y
1+(-1)=0
d)n²+n-7=3n²-n-9-n+16 dla n= -½
n²-3n²+n+n+n=-9+16 +7
-2n² +3n=14
-2(-1/2)² -1,5= 14
4,5 -14 -1,5= -11





ostatnie może byc zle
15 3 15